Training biochemistry students in experimental developmental biology: Induction of cardia bifida formation in the chick embryo - Palmquist Gomes, Paul; Guadix-Domínguez, Juan Antonio; Pérez-Pomares, José María (Wiley, 2021)
A high variety of experimental model organisms have been used in developmental biology practical lectures. The work with developing embryos is crucial to make students aware of the multiple biological phenomena underlying normal animal embryogenesis and morphogenesis and represent a unique experimental platform to analyze the impact of molecular signaling in the regulation of all these processes. In particular, Biochemistry undergraduate students enjoy both practical and theoretical lectures on the molecular mechanisms of embryonic development, as that allows them for the integration of crucial molecular concepts (e.g. signaling and signal transduction mechanisms; molecular patterning of development) into the dynamic and progressive context of animal embryonic ontogenesis. Accordingly, it is important to carefully design practical laboratory lectures in developmental biology, as these are a unique pedagogical tools fostering the interests of the students in this subject. This study describes the design, implementation, and evaluation of a two-session laboratory practical activity performed by Biochemistry undergraduate students at University of Málaga (Spain). In this practical activity, which takes advantage of the unique characteristics of the chick embryo, students learn how the vertebrate heart forms from the fusion of two bilateral-symmetric cardiac progenitor pools under the guidance of the underlying endoderm. This cheap and easy practical laboratory activity provides relevant visual information on how experimental manipulations can severely influence anatomical form during organ development, as well as an excellent experimental setting to test molecular regulation of morphogenesis in an ex vivo (ex ovo) context.
Keywords: Pollos - Embriología - Congresos; Cardia bifida; Developmental biology; Heart development; Laboratory active learning; Molecular regulation of embryogenesis